Analysis of Land Use Migration Change in Ganjiang River Basin - HE Hao; LIU Weilin; LI Xiang; ZHANG Jingrong; YANG Qing; TU Xuke; LIU Jianwu; LIU Lina (Renmin Zhujiang)
Land use/cover change is an important representation of interactions between humans and the natural environment,and its change characteristics profoundly influence regional ecological security and sustainable socio-economic development.Based on the land use data of the Ganjiang River Basin from 1980 to 2018,the spatio-temporal changes in land use in this basin are analyzed by ArcGIS spatial analysis method.The results show that forest land and cultivated land are the main land types in Ganjiang River Basin.The areas of the two land types decrease,with constantly increasing construction land area.The comprehensive dynamic index of land use in the basin is increasing,which indicates accelerating land use changes.The types of land use conversion are mainly the transfer from cultivated land and forest land to construction land,the mutual transfer of forest land and grassland,and the transfer from forest land to cultivated land,with some cultivated land transferred to waters.The centers of gravity of grassland,waters,and construction land change significantly,and are moving northwest,southwest,and southeast respectively with phased moving speeds.The research results can provide scientific references for ecological environment protection,and planning and management of water and land resources in the Ganjiang River Basin.